2010
DOI: 10.1128/jvi.02536-09
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Serological Characterization of a Human Theiler's-Like Cardiovirus Associated with Diarrheal Disease

Abstract: Cardioviruses (e.g., Theiler's murine encephalomyelitis virus [TMEV]) are members of the Picornaviridae family that cause myocarditis and encephalitis in rodents. Recently, several studies have identified human cardioviruses, including Saffold virus (SAFV) and a related virus named human TMEV-like cardiovirus (HTCV). At least eight cardiovirus genotypes are now recognized, with SAFV and most strains of HTCV belonging to genotypes 1 and 2, respectively; genotype 2 strains are the most common in the population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 25 publications
(58 reference statements)
0
56
0
Order By: Relevance
“…In several cases, SAFV has been detected in addition to other viruses known to cause gastroenteritis, thus hindering interpretation regarding SAFV infection and observed pathology (Chiu et al, 2008;Drexler et al, 2008;Ren et al, 2009). SAFV-2 has recently been linked to infection in a child with diarrhoea and vomiting, based on an acute seroconversion event supporting an association between this virus and diarrhoeal disease (Chiu et al, 2010). Although SAFV-3 was the only viral agent identified in five of 15 of the unexplained cellculture samples in this study, it cannot be concluded that these viruses were causing illness or clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases, SAFV has been detected in addition to other viruses known to cause gastroenteritis, thus hindering interpretation regarding SAFV infection and observed pathology (Chiu et al, 2008;Drexler et al, 2008;Ren et al, 2009). SAFV-2 has recently been linked to infection in a child with diarrhoea and vomiting, based on an acute seroconversion event supporting an association between this virus and diarrhoeal disease (Chiu et al, 2010). Although SAFV-3 was the only viral agent identified in five of 15 of the unexplained cellculture samples in this study, it cannot be concluded that these viruses were causing illness or clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…2). In the USA, it has been shown that 91 % of adults carry antibodies against SAFV-2, with 80 % of studied individuals generating neutralizing antibodies against this genotype (Chiu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, whereas SAFV-3 has shown efficient growth and a clear cytopathic effect (CPE) in several cell lines, SAFV-2 strains are difficult to propagate and the detection of SAFV-2 has been mainly performed using molecular methods (5,9,12,(18)(19)(20). Chiu et al succeeded in isolating the SAFV-2 HTCV-UC6 strain only after the addition of monoclonal anti-cytokine antibodies (20).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
“…Chiu et al succeeded in isolating the SAFV-2 HTCV-UC6 strain only after the addition of monoclonal anti-cytokine antibodies (20). Although they analyzed viral tropism in vitro by using the HTCV-UC6 strain and 11 cell lines, they observed that viral replication was quite limited (20).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
See 1 more Smart Citation